Pengaruh Pembelajaran Active Deep Leaner Experience (ADLX) Terhadap Hasil Belajar Siswa SDIT Permata Mulia Mojokerto - Noor Lailie; Galuh Katika Dewi (STKIP Singkawang, 2022)
The purpose of this study was to observe the effect of ADLX (Active Deep learner Experience) learning toward the output of SDIT Permata’s students. The method used in this study is Wilk Shapiro normality test, homogeneity test and T-independent test. The sample is the third grade students of SDIT Permata Mulia. It consists of two group. First, the third grade (Hasan) students as a control group and second, the third grade (Husein) students as experiment group. The result of this study shows that the output of experiment group is better than the control group, because of using ADLX learning. While the control group uses conventional learning. This result can be analyzed from the difference of the score average of the two group. The score average of the control group is 79,33, however the the score average of the experiment group is 89,61. Beside, T-independent test shows that T-count (-17.289) is less than T-table (2,728), it means that there is a significant difference in output between an experiment and a control group. In conclusion, there is an effect of ADLX (Active Deep learner Experience) learning to a students’ output.